2010
DOI: 10.1007/s00248-010-9720-8
|View full text |Cite
|
Sign up to set email alerts
|

Root Colonization by Pseudomonas sp. DSMZ 13134 and Impact on the Indigenous Rhizosphere Bacterial Community of Barley

Abstract: Over the last few decades, the ability of rhizosphere bacteria to promote plant growth has been considered to be of scientific, ecological, and economic interest. The properties and mechanisms of interaction of these root-colonizing bacteria have been extensively investigated, and plant protection agents that are based on these bacterial strains have been developed for agricultural applications. In the present study, the root colonization of barley by Pseudomonas sp. DSMZ 13134, that is contained in the commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 56 publications
2
43
0
1
Order By: Relevance
“…The absence of response after BE application was observed in many other experiments [45,48,49] and in particular in soils characterized by extraordinary low levels of available P (20 mg kg −1 or lower) or that were limiting in other soil nutrients [10,50,51]. In contrast, other studies have shown that for maize and other crops, the application of BEs was more efficient in the absence of added P fertilizers [36][37][38]. However, in these cases, soil P availability was distinctly higher and P CAL ranged between 35 and 45 mg/kg.…”
Section: Moderate Effects In the Absence Of Added P (P0 Be1-3)mentioning
confidence: 89%
See 2 more Smart Citations
“…The absence of response after BE application was observed in many other experiments [45,48,49] and in particular in soils characterized by extraordinary low levels of available P (20 mg kg −1 or lower) or that were limiting in other soil nutrients [10,50,51]. In contrast, other studies have shown that for maize and other crops, the application of BEs was more efficient in the absence of added P fertilizers [36][37][38]. However, in these cases, soil P availability was distinctly higher and P CAL ranged between 35 and 45 mg/kg.…”
Section: Moderate Effects In the Absence Of Added P (P0 Be1-3)mentioning
confidence: 89%
“…The strain Trichoderma harzianum Rifai 1295-22 (T22) has demonstrated abilities to increase the solubilization of sparingly soluble calcium phosphates [34] and to promote plant growth in various plant species [35,36] including maize [37]. The strain Pseudomonas DSMZ 13134 is an efficient root colonizer [38] and has been shown to solubilize inorganic phosphate under in vitro conditions [39]. Moreover, it has recently shown the potential to improve plant growth and phosphorus acquisition when inoculated to maize [10,25].…”
Section: Be Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an investigation across a number of field studies involving wheat showed that P. bilaii does not significantly affect P uptake and yield [35]. Gram-negative gammaproteobacteria of the genus Pseudomonas are ubiquitous bacteria in soil, are known to proliferate greatly in the rhizosphere [36] and have been studied for their plant growth-promoting activities for many years [37]. Bacteria from this genus have been observed to increase plant productivity under P-limiting conditions [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…DSMZ 13134 and its transient impact on the dominant root-associated bacterial community has been shown (Buddrus-Schiemann et al 2010). However, there have been no investigations into the effect of root colonization of Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%